Performance of spring-summer blackgram (Vigna mungo) with nutrient fortification under eastern Indian plains - BANERJEE, PURABI; KUMARI, V VISHA; NATH, RAJIB (The Indian Journal of Agricultural Sciences, 2023)
Blackgram [Vigna mungo (L.) Hepper] is an important grain legume in Indian sub-continent imparting nutritional benefits from ancient times. A field experiment was conducted with blackgram in spring-summer seasons during 2020 and 2021 in Bidhan Chandra Krishi Viswavidyalaya, West Bengal with two sowing dates in March in main plot, two soil applications of Co at 4 kg/ha in sub-plot and five foliar spray levels of 1.25% K and 0.2% B in sub-sub plot in a split-split plot design to explore the effects of Co, K and B in improving growth, physiology, production, quality and production economics of the crop. Pooled analysis indicated that March first week sowing as well as soil application of Co and foliar K+B fortifications separately achieved significantly higher (P=0.05) plant height, dry matter accumulation, root nodulation, branches/plant, pods/plant, seeds/pod, test weight, total chlorophyll and nitrate reductase contents, net photosynthetic rate, physiological efficiency, yield, seed nutrients and protein contents, economic returns and benefit-cost ratio. Seed protein content was a linear function of root nodule numbers explaining about 84.05% variation. Sowing of blackgram during March first week with soil application of Co and foliar K+B spray is a promising agronomic management to improve blackgram production in a cost-effective way under Gangetic plains of Eastern India.